(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The illicit trade in tobacco products poses a significant challenge to global health by undermining tobacco control efforts, reducing government revenues, and increasing the accessibility of unregulated tobacco products. To address this issue effectively, we introduce the Illicit Trade in Tobacco Products Indicator (ITTPI), a comprehensive tool designed to visualize and track illicit tobacco trade patterns worldwide. The ITTPI integrates data on counterfeit cigarettes, contraband activities, and risk factors associated with these illegal practices. By leveraging an interactive mapping system, this indicator facilitates real-time monitoring of high-risk regions and channels involved in illicit trade. Our study demonstrates how ITTPI can be applied across diverse contexts to identify hotspots of illicit activity and predict future trends based on historical data analysis. This approach not only aids law enforcement agencies but also informs policymakers about targeted interventions needed to strengthen regulatory frameworks against tobacco smuggling. By enhancing transparency and coordination among international stakeholders, the ITTPI offers a promising solution for combating the global problem of illicit tobacco trade while supporting broader public health objectives aimed at reducing smoking prevalence worldwide.